Phonetic Transcription of Fricatives and Plosives for Gujarati and Marathi Languages - Patil, H. A.; Madhavi, M. C.; Malde, K. D.; Vachhani, B. B. (2012 International Conference on Asian Language Processing (IALP), 2012)
This paper addresses phonetic transcription related issues in Gujarati and Marathi (Indian Languages). Some adhoc approaches to fix relationship between the general alphabetical symbols and phonetic symbols may not always work. Hence, some research issues like ambiguity between frication and aspirated plosive are addressed in this paper. The anusvara in both of these languages are produced based on the immediate following consonant. Implication for this finding for the problem of phonetic transcription is presented. Furthermore, the effect of dialectal variations on phonetic transcription is also analyzed for Marathi. Finally, some examples of phonetic transcription for sentences of these two languages are presented.